Sequential Pituitary MR Imaging in Sheehan Syndrome: Report of 2 Cases - Kaplun, J.; Fratila, C.; Ferenczi, A.; Yang, W.C.; Lantos, G.; Fleckman, A.M.; Schubart, U.K. (American Journal of Neuroradiology, 2008)
SUMMARY: We present the evolution of pituitary changes in the cases of 2 patients with Sheehan syndrome as assessed by MR imaging. Both patients had severe postpartum hemorrhage, symptoms of pituitary gland apoplexy, and hypopituitarism. Sequential MR imaging demonstrated evidence of ischemic infarct in the pituitary gland with enlargement followed by gradual shrinkage during several months, to pituitary atrophy.